Kompetensi Kleder Dalam Peningkatan Aspek Keselamatan Dan Keamanan Pelayaran Kapal Khusus Ternak - Ade Mardani Putra; Aji Ludro Tamtomo; Harri Mochammad Mansur; Joko Sulistianto (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
This research aims to give a recommendation competition requirement which needed by kleder in improving of safety aspect cattle ship. The research method uses descriptive qualitative with literature study. Observation and interview done for evaluation of cattle transportation policy who employs the kleder on the ship. The observation was conducted by captain and crew. The collected data is then processed and analyzed using policy analysis. The result of the research is that an increase in Kleder’s competence is absolutely necessary not only in terms of handling livestock but also in the basic skills of shipping safety and security on ships. In improving the safety and security aspects of livestock shipping, crew members are required to have a basic certification of shipping safety and security and be registered in an emergency certificate in order to comply with the provisions on manning. In addition, there is a need for serious attention and coordination among institutions, practitioners, ship owners, livestock owners and other related parties to issue appropriate policies regarding the status of kleders on board ships.